Work in progress report of a multicentre retrospective observational study to evaluate the association between the airflows and the intrapleural pressures digitally recorded after video-assisted lobectomy. (9th May 2021) - Bertolaccini, Luca; Viti, Andrea; Bertoglio, Pietro; Imperatori, Andrea; Morelli, Angelo; Zaraca, Francesco; Spaggiari, Lorenzo; Crisci, Roberto; ,
Abstract:  : OBJECTIVES: Digital chest drainage systems allow real-time and continuous monitoring and recording of air leak flow rate and intrapleural pressure (IPP) from the immediate postoperative period to the chest drainage removal. A multicentre retrospective observational analysis of consecutive patients undergoing pulmonary lobectomy for lung cancer was performed to evaluate the association between the airflow and IPP digitally recorded during the immediate postoperative period after video-assisted thoracic surgery (VATS) lobectomy for lung cancer. Here, we present a work in progress report. METHODS: All patients treated with VATS lobectomies for lung cancer were included. Multiple airflow measurements and minimum and maximum IPP through the chest tubes were digitally monitored and recorded using microelectronic mechanical sensor technology. The PALs were defined as an air leak lasting >5 days from the conclusion of the surgical procedure. The cessation of air leaks was defined as an airflow <10 ml/min during 6 consecutive hours. RESULTS: This analysis comprised 76 patients who underwent VATS lobectomy for lung cancer. Nineteen patients (25%) showed prolonged air leaks (PAL) (≥5 days). The operative time was higher in the PAL group (mean difference = 44 min) without a statistically significant difference. Before the 7th postoperative hours, there were no statistically significant differences in IPPs. CONCLUSIONS: Patients with PAL showed less negative IPP in the first 24 postoperative hours. Therefore, the 7th—24th postoperative hours were critical in PAL prediction since the mechanism for PAL seems to develop after the 7th postoperative hour.